UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL 96% DAUN RAMANIA (Bouea macrophylla Griffith.) DARI DAERAH KALIMANTAN SELATAN DENGAN METODE DPPH - Saftia Aryzki; Setia Budi; Yanti (Jurnal Insan Farmasi Indonesia, 2023)
Ramania (Bouea macrophylla Griffith.) is a herbal plant that has antioxidant properties and inhibits free radicals. This research aims to determine the antioxidant potential of ramania leaf ethanol extract by looking at the IC50 value. Ramania leaves were extracted using the maceration method using 70% ethanol solvent. Antioxidant potential is determined using the DPPH (1,1-diphenyl-2-picrylhydrazyl) method by comparing vitamin C which has been proven to have very potent free radical potential. The ramania leaves made had a concentration of 10% and then diluted to a concentration of (20,40,60,80,100) µg/mL. 2 mL of each infusion was taken and reacted with 2 mL of 50 µg/mL DPPH solution in an aluminum-lined test tube for a period of time (30 minutes). The results showed that the IC50 value of the ethanol extract of ramania leaves was 0.8126 ± 78.56387 µg/mL. The IC50 value obtained was compared with the inhibition value of the vitamin C solution made with varying concentrations (2,4,6,8,10) µg/ mL, based on this value, ramania leaf extract from the Sleman area is categorized as very potent so it can be developed as a source of antioxidants from natural ingredients.